24‐4: Foldable AMOLED Display Utilizing Novel COE Structure. Issue 1 (30th May 2018) - Xu, Chuan X.; Shu, Shi; Lu, Jiang N.; Yuan, Guang C.; Yao, Qi; Wang, Lei; Xu, Zhi Q.; Sun, Zhong Y.
Abstract : A 5.46inch WQHD foldable AMOLED display having thin thickness, wide color gamut, high brightness and low reflectivity was obtained. These properties, which outperform those of a conventional RGB OLED and circular polarizer system, were achieved with a novel structure of RGB emitter, thin film encapsulation and low temperature color filter directly patterned on TFE.